A comparison of Demirjian and Willems age estimation methods in a sample of Brazilian non-adult individuals. (June 2021) - Gonçalves, Laura Sanches; Machado, Ana Luísa Rezende; Gaêta-Araujo, Hugo; Recalde, Tamara Soledad Frontanilla; Oliveira-Santos, Christiano; Silva, Ricardo Henrique Alves da
Highlights: Agreement between the ages estimated by the methods of Demirjian and Willems and the real age of Brazilian individual. Dermijian's and Willems' methods are reproducible. Both methods overestimate the ages. Willems' method presented a lower overestimation for being a development of the Demirjian's method. The agreement between the estimated ages and the real ages was higher for males when compared to girls. Abstract: Age estimation methods take into account the organism variation during its development or involution. Dental methods can often be considered, because the dental development presents a series of recognizable events with small variation. Each method presents a different methodological proposal, so it is important to consider the type of dentition, the presence or absence of teeth, available information and the method's validation, as dental development may differ among different populations. The present study aimed to assess the agreement between the ages estimated by the methods of Demirjian and Willems and the real age of Brazilian individual. To compose the sample and apply the methods, 220 panoramic radiographs of individuals from 6 to 16 years were selected, being 110 females and 110 males. After applying the methods by three examiners, it was possible to observe that both methods showed high correlation values ​​among males. However, the results for female brought lower values. In addition, the Willems' method was more suitable to the population considered when compared to the Demirjian's method, despite the overestimation of real ages by both methods.